Getting nothing from something: Unfulfilled promises of current dominant approaches to entrepreneurial decision-making - Richard J. Arend (Administrative Sciences, 2020)
We provoke. In this conceptual piece, we challenge the value of two dominant models of the entrepreneurial process that have existed over the past two decades-the creativity school and the logic of effectuation. We point out their weaknesses and their unfulfilled promises, and we argue for the field to move on forward with different ideas. We identify the lessons our field should learn so as to minimize the possibility of potentially detrimental model dominance in the future. We then outline three alternative approaches to modeling entrepreneurial decision-making that suggest further skills and policies required in improve the entrepreneurial process.
Keywords: 350; competitive advantage; critical assessments; entrepreneurial decision-making; opportunity identification; resource-based view